Exploring Psychological and Policy Drivers of EV Conversion on Urbanites Professionals - Prayogo Probo Susanto; Rubin Sanjaya; Angella Permata Cyntia Kristin; Peri Akbar Manaf (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The paper examines the direct influence of attitude on purchase intention toward EV adoption in Indonesia. This article also attempts to analyze the impact of social influence and government incentives on attitude and self-efficacy on perceived behavioral control. For research purposes, quantitative research was applied by conducting an empirical survey with the active participation of 191 urbanite car owners who live in metropolitan Jakarta in Indonesia. We use model principal component analysis (PCA) with partial least squares–structural equation modelling (PLS–SEM) (SmartPLS) for measurement and structural model analysis. This study explains how psychological considerations influence EV consumers' buying behavior and attitude more than policy drivers. The result shows how metropolitan consumers consider the interactions between attitude and purchase intention towards adopting electric vehicles in Indonesia. The practical implications of the research findings could provide managerial insight targeting consumers with the same characteristics, considering the size of this consumer in Southeast Asia, South Asia, and developing countries in Africa and South America (at least 10-15 metropolitan cities).